1) 94.326-123×8: [848: 4-(a×100+5×2) ]+838149: 3=373.217
2) [(a-12.324×3): 4+26.193×5]-22.599×5=31.436
3) 200-(64+a×12+4×11) =2×(50-24×2+13×5-9×5)
va roog
Răspunsuri la întrebare
1)
94 326 - 123 × 8 : [ 848 : 4 - ( a × 100+ 5 × 2) ] + 838 149 : 3=373 217
94 326 - 984 : [ 212 - ( a × 100 + 10 ) ] + 279 303 = 373 217
94 326 - 984 : [ 212 - ( a × 100 + 10 ) ] = 373 217 - 279 217
94 326 - 984 : [ 212 - ( a × 100 + 10 ) ] = 93 834
984 : [ 212 - ( a × 100 + 10 ) ] = 94 326 - 93 834
984 : [ 212 - ( a × 100 + 10 ) ] = 492
212 - ( a × 100 + 10 ) = 984 : 492
212 - ( a × 100 + 10 ) = 2
a × 100 + 10 = 212 - 2
a × 100 + 10 = 210
a × 100 = 210 - 10
a = 200 : 100
a = 2
______________________________________
2)
[ ( a - 12 324 × 3) : 4 + 26 193 × 5 ] - 22 599 × 5 = 31 436
[ ( a - 36 972 ) : 4 + 130 965] - 112 995 = 31 439
( a - 36 972 ) : 4 + 130 965 = 31 439 + 112 995
( a - 36 972 ) : 4 + 130 965 = 144 434
( a - 36 972 ) : 4 = 144 434 - 130 965
( a - 36 972 ) : 4 = 13 469
a - 36 972 = 13 469 × 4
a - 36 972 = 53 876
a = 53 876 + 36 972
a = 90 848
_________________________________
3)
200 - ( 64 + a × 12 + 4 × 11 ) = 2 × ( 50 - 24 × 2 + 13 × 5 - 9 × 5 )
200 - ( 64 + a × 12 + 44 ) = 2 × ( 50 - 48 + 65 - 45 )
200 - ( 64 + a × 12 + 44 ) = 2 × ( 2 + 65 - 45 )
200 - ( 64 + a × 12 + 44 ) = 2 × ( 67 - 45 )
200 - ( 64 + a × 12 + 44 ) = 2 × 22
200 - ( 64 + a × 12 + 44 ) = 44
64 + a × 12 + 44 = 200 - 44
64 + a × 12 + 44 = 156
64 + a × 12 = 156 - 44
64 + a × 12 = 112
a × 12 = 112 - 64
a × 12 = 48
a = 48 : 12
a = 4